Optimization of Thermoreversible In Situ Nasal Gel of Timolol Maleate - Jagdale, Swati (Scientifica (Cairo), 2016)
Nasal route had shown better systemic bioavailability due to its large surface area, porous endothelial membrane, high total blood flow, and avoidance of first-pass metabolism. Timolol maleate is a beta blocker used primarily in the treatment of hypertension. Drug undergoes extensive hepatic first-pass metabolism (80%). The drug has half-life of 4 hrs. Oral bioavailability of timolol maleate is 61%. The aim of the present study was to optimize controlled release in situ nasal delivery for timolol maleate. HPMC and Poloxamer 407 were selected as polymer in formulation of thermoreversible in situ nasal gel. Optimization was carried out using 3(2) factorial design. It was observed that formulations f1 and f4 revealed the highest % drug release, that is, 93.57% and 91.66%, respectively. Factorial design study indicated that the drug release and viscosity were most significant dependent factors. Ex vivo diffusion study through nasal mucosa indicated 67.26 ± 2.10% and 61.07 ± 2.49% drug release for f1 and f4 formulations. f1 was the optimized batch. This batch thus can act as a potential nasal delivery with enhanced bioavailability for the drug.